Determinants of pesticide exposure among workers in floriculture industry in rural Maharashtra - Dandekar, Ashlesha A.; Raje, Swati S.; Kadale, Prajakta G. (International Journal Of Community Medicine And Public Health, 2019)
Background: Pesticides are extensively used in floriculture where workers are mostly unskilled and may not have appropriate knowledge about safety. Acute accidents during spraying are reported, chronic exposure goes unnoticed. There are not many Indian studies regarding health risks and safety practices among floriculture workers in India. Hence this study to assess pesticide exposure, to find their determinants and suggest appropriate preventive measures. Methods: Study was cross sectional in Floriculture Park, Talegaon (D), Pune, Maharashtra, India using cluster sampling from February 2018 to July 2019. Prevalence of morbidities being 63% sample size was calculated as 111 (allowable error 15%). Socio-demographic, work and health related variables were recorded using a pretested structured questionnaire. Clinical examination and laboratory investigations were done by medical experts. Results: A total of 118 workers participated. Only half (51.2%) were using personal protective devices. None were following reentry guidelines. 13.3% males and 4.1% females had low serum cholinesterase level which is a biomarker of pesticide exposure. Sprayers had significantly high risk of low serum cholinesterase levels (OR=3.31) as compared to others. With exposed subjects which included both sprayers as well as polyhouse workers the association increased with OR=4.27. However association was not significant when working in polyhouse alone was considered as a risk factor (OR=1.256). Conclusions: Presence of exposure was the only factor that had a statistically significant association with low Serum Cholinesterase levels. Safe occupational practices like use of personal protective devices, rotation of exposed workers, monitoring of serum cholinesterase levels and health education of workers should be undertaken.